PENINGKATAN PHYSICAL HEALTH MASYARAKAT MELALUI SENAM LANJUT USIA (LANSIA) - Hartono Hadjarati; Nurkhoirah Nurkhoirah; Meri Haryani (Universitas Muhammadiyah Luwuk, 2023)
Exercise can improve a person's body fitness if done regularly and regularly, someone who has been trained with routine exercise will have a more immune immune system than someone who does not exercise, as well as the elderly also need exercise even if it's just walking which is done regularly and measured. The purpose of implementing community service activities is to increase knowledge and increase physical activity through elderly gymnastics. This activity was carried out in Oluhuta Village, Kabila Sub-district, Bone Bolango Regency, Gorontalo Province on May 13, 2023, with participants aged 45-60 years. The method of implementation of PkM is by lecture, demonstration (practice) and video recording. The first stage of PkM implementation is survey and observation to the village government, then preparation for implementation and implementation of PkM as well as monitoring and evaluation. The results of observations show that elderly gymnastics training can have an effect on increasing physical activity so that there is an increase in Physical Health of the elderly in Oluhuta Village. Implementation of PkM in the form of lectures and practice of elderly gymnastics, easily accepted by the training participants